PROYEK PROFIL PELAJAR PANCASILA SEBAGAI SARANA PENINGKATAN KARAKTER SISWA: TINJAUAN LITERATUR SISTEMATIS - Yuliwinarti, Evy Marita; Wahyu Sukartiningsih; Hitta Alfi Muhimmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character education is one of the main priorities in the education system in Indonesia. Currently, character education in Indonesia faces significant challenges. Character education creates a school environment that supports the ethical and responsible development of learners, through concrete examples and teaching of good universal values. The Pancasila Learner Profile is a concept developed by the Indonesian government to strengthen character education in schools. The research method used in this study is SLR (Systematic Literature Review). Data collection is done by identifying or reviewing articles that have the same research topic. The article used is the latest publication period 2022-2024. This article contains the implementation of the Pancasila Student Profile Project through three stages, namely planning, implementation and evaluation. The implementation stage also goes through several steps, namely: (1) Opening, (2) Delivery of P5 material, (3) Preparation of the P5 program. (4) P5 practice. (5) Evaluation of the level of teacher understanding of P5. In addition, there were several supports and obstacles that occurred during the implementation of P5. Supports include: 1) consistency and commitment from the school to implement P5; 2) collaboration of students and teachers; 3) the ability of teachers to implement P5; 4) active participation from parents; 5) support from the community and the environment, and; 6) complete facilities and infrastructure. While the obstacles found were: (1) differences in perceptions between facilitators due to the lack of preparedness of facilitators' mindset in implementing P5; (2) inadequate resources; (3) resistance from some students or parents to changes in learning approaches; (4) budget limitations; and (5) difficulties in character assessment. Keywords: Independent Curriculum, Pancasila Learner Profile Project, Student Character